2006
DOI: 10.1177/1545968306286976
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Function Following Grafting of Human Bone Marrow-Derived Stromal Cells into the Injured Spinal Cord

Abstract: This study evaluates functional recovery after transplanting human bone marrow-derived stromal cells (BMSCs) into contusion models of spinal cord injury (SCI). The authors used a high-throughput process to expand BMSCs and characterized them by flow cytometry, ELISA, and gene expression. They found that BMSCs secrete neurotrophic factors and cytokines with therapeutic potential for cell survival and axon growth. In adult immune-suppressed rats, mild, moderate, or severe contusions were generated using the MASC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
156
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 203 publications
(174 citation statements)
references
References 80 publications
14
156
1
3
Order By: Relevance
“…In our study, BMSCs in the dorsal gray commissure, presenting proximal to both the sacral parasympathetic preganglionic neurons and the spinal EUS pattern generator, may promote the formation of the switch to coordinate bladder contraction and EUS relaxation by expressing neuronal and astroglial markers 18 or secreting neurotrophic factor and cytokine. 19 In the current study, we did not examine how these BMSCs differentiated after transplantation. Clearly, this is a limitation of the study.…”
Section: Discussionmentioning
confidence: 93%
“…In our study, BMSCs in the dorsal gray commissure, presenting proximal to both the sacral parasympathetic preganglionic neurons and the spinal EUS pattern generator, may promote the formation of the switch to coordinate bladder contraction and EUS relaxation by expressing neuronal and astroglial markers 18 or secreting neurotrophic factor and cytokine. 19 In the current study, we did not examine how these BMSCs differentiated after transplantation. Clearly, this is a limitation of the study.…”
Section: Discussionmentioning
confidence: 93%
“…1 Somewhat surprisingly, MSCs have received considerable interest as possible donor cells in the development of cell transplantation therapies for spinal cord injury (SCI). [2][3][4][5][6][7] There are, however, a number of reasons for this. First and foremost, MSC transplantation has been demonstrated to enhance axonal regeneration and promote functional recovery in a variety of animal models of SCI.…”
Section: Introductionmentioning
confidence: 99%
“…First and foremost, MSC transplantation has been demonstrated to enhance axonal regeneration and promote functional recovery in a variety of animal models of SCI. [2][3][4][5][6][7] These studies have shown that transplanted MSCs integrate into host tissue following transplantation, supporting and remyelinating axons that traverse the injury site. MSCs also synthesize a number of growth factors that may contribute to tissue sparing and axonal regeneration, including nerve growth factor and brain-derived neurotrophic factor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because MSC can be easily obtained using a simple bone marrow aspiration and show an extensive capacity for expansion in vitro, these cells have been considered as candidates for cell therapy. So far, MSC have been used with varying success to improve neurological (7)(8)(9), cardiovascular (10), blood-related (11,12) and musculoskeletal disorders (13,14).…”
mentioning
confidence: 99%